2019
DOI: 10.14283/jfa.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Frailty and Mild Cognitive Impairment in the Elderly: A Systematic Review

Abstract: Introduction: Physical frailty (PF) appears to be associated with low cognitive performance and mild cognitive impairment (MCI). This review evaluated and synthesized the evidence of studies investigating the association between PF and MCI, the prevalence of both conditions and the rate of conversion of healthy older adult to one of them during the follow-up. Methods: A systematic review was performed according to the PRISMA recommendations in the Pubmed, SciELO and LILACS databases. Five studies were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Several shreds of evidence demonstrated that frailty and cognitive impairment are intrinsically related, since frailty is known to increase risk of cognitive decline, and cognitive decline may increase risk of frailty and have an impact on the trajectory of frailty (as recent reviews see Kiiti Borges et al, 2019 ; Welstead et al, 2020 ; Bu et al, 2021 ). The concept of simultaneous presence of frailty and cognitive impairment or cognitive frailty was initially proposed in 2013 by the International Institute of Nutrition and Aging and the International Geriatrics Association (IANA), defined by the presence of physical frailty and cognitive impairment, and exclusion of concurrent dementia ( Kelaiditi et al, 2013 ).…”
Section: Cognitive Frailty: the Potential Role Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Several shreds of evidence demonstrated that frailty and cognitive impairment are intrinsically related, since frailty is known to increase risk of cognitive decline, and cognitive decline may increase risk of frailty and have an impact on the trajectory of frailty (as recent reviews see Kiiti Borges et al, 2019 ; Welstead et al, 2020 ; Bu et al, 2021 ). The concept of simultaneous presence of frailty and cognitive impairment or cognitive frailty was initially proposed in 2013 by the International Institute of Nutrition and Aging and the International Geriatrics Association (IANA), defined by the presence of physical frailty and cognitive impairment, and exclusion of concurrent dementia ( Kelaiditi et al, 2013 ).…”
Section: Cognitive Frailty: the Potential Role Of Mirnasmentioning
confidence: 99%
“…Frailty is a clinical syndrome with different definitions, generally referred as a state of increased vulnerability to stressors that results from a decreased physiological reserve in multiple organs and systems, leading to a limited capacity to meet homeostatic demands ( Clegg et al, 2013 ; Proietti and Cesari, 2020 ). Although frailty and cognitive impairment could be considered as distinct clinical states, converging evidence has shown a close epidemiological association between these conditions ( Halil et al, 2015 ; Kiiti Borges et al, 2019 ; Miyamura et al, 2019 ). This led to the generation of the term “cognitive frailty,” defined as a heterogeneous clinical condition characterized by the concomitant presence of both physical frailty and cognitive impairment ( Kelaiditi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related cognitive decline is a robust predictor of mortality in older people, even when it does not progress to dementia [ 4 ]. Cognitive impairment has also been associated with an increased likelihood of adverse outcomes, including frailty [ 5 ], serious fall-related injury [ 6 ] and disability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have verified that older adults with PF perform worse on global cognition ( 13 , 14 ) and are more likely to experience cognitive decline( 15 19 ) and cognitive impairment ( 20 22 ). In addition, there is also evidence that cognitive function can also have an impact on frailty in older people ( 23 25 ). However, few studies have explored the specific mechanisms of frailty and cognitive function.…”
Section: Introductionmentioning
confidence: 99%